2022
DOI: 10.1021/acs.inorgchem.2c01967
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Decomposition in a Family of Molybdenum Precursor Compounds

Abstract: The bis­(tert-butylimido)-molybdenum­(VI) framework has been used successfully in the design of vapor-phase precursors for molybdenum-containing thin films, so understanding its thermal behavior is important for such applications. Here, we report the thermal decomposition mechanism for a series of volatile bis­(alkylimido)-dichloromolybdenum­(VI) adducts with neutral N,N′-chelating ligands, to probe the stability and decomposition pathways for these molecules. The alkyl groups explored were tert-butyl, tert-pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(57 citation statements)
references
References 118 publications
0
57
0
Order By: Relevance
“…It is well known that bis(tert-butylimido)molybdenum(VI) adducts decompose to yield isobutylene, 7,10,15,16,33,34 assuming that lower-temperature "ancillary ligand-centered" decompositions do not occur. Therefore, isobutylene was anticipated to be the primary decomposition product in the thermolysis of 1.…”
Section: Volatility and Thermal Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that bis(tert-butylimido)molybdenum(VI) adducts decompose to yield isobutylene, 7,10,15,16,33,34 assuming that lower-temperature "ancillary ligand-centered" decompositions do not occur. Therefore, isobutylene was anticipated to be the primary decomposition product in the thermolysis of 1.…”
Section: Volatility and Thermal Stabilitymentioning
confidence: 99%
“…tert-Butylamine is a major decomposition product in the thermolysis of ( t BuN)2MoCl2 adducts. 16,33 It forms via an intramolecular γ-H transfer (of a t BuN proton) to another imido moiety, resulting in a tert-butylamido ligand and a nitrido (Mo≡N) moiety. 16 A previous report, based specifically on the thermolysis of ( t BuN)2Mo(Pz) (A), 10 proposed that γ-H activation, to yield isobutylene and a hydrogen-terminated imido (Mo=NH), occurs first.…”
Section: Volatility and Thermal Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Alignment of the dipoles in molecules of 3 results in the head to tail arrangement shown in the Figure . Compounds 1 and have the same general structure, and we have previously shown that upon vaporization they lose their coordinative ligands, resulting in the formation of the same gas phase species, [( t BuN)Mo(μ-N t Bu)Cl2]2. 13,14 Therefore, volatilization of eutectic mixtures of these compounds (1 or 3 with 2) should result in the same surface species and uniform film composition, upon deposition.…”
mentioning
confidence: 99%